Pregnancy diagnosis in goats (Capra hircus) using barium chloride and progesterone-based kit in Bangladesh - Akther, Sonia; Munsi, Md Nuruzzaman; Rahman, Md Habibur; Hassan, Md Zakir (Asian Journal of Medical and Biological Research, 2022)
The study was conducted to develop a technique for early diagnosis of pregnancy in goats from July 2016 to June 2017. About 100 goats of different age groups were randomly selected for the trial and goats were categorized under four groups according to their gestation lengths (0.5 to 1 month, >1 to 1.5 months, >1.5 to 2 months and >2 to 2.5 months). Blood from jugular vein and morning urine samples were collected from four groups and brought to the laboratory, and serum was separated from the clotted blood. Then 1%, 1.5% and 2% barium chloride solution were prepared and test was done by using 1 ml barium chloride of each concentration mixing with 1 ml of urine sample, and allowed for 5 and 10 minutes for interpretation. Presence of precipitation was interpreted as negative for pregnancy and absence of precipitation was interpreted as positive for pregnancy. For each blood sample, 3-5 drops of serum was added in each sample insertion hole of the Bovipreg kit and 5 minutes was allowed to observe the presence of one or two red line in the kit. One red line was interpreted as negative pregnancy and two red lines were interpreted as positive pregnancy. In our study 1% barium chloride, showed 93.5% accuracy, whereas 1.5% barium chloride provided 92% accuracy for the goats having 0.5 to 1 month of gestation. In case of 2% barium chloride, the highest accuracy was 91.5% for the goats having >1 to 1.5 month of gestation. Conversely, the accuracy for progesterone-based early pregnancy diagnostic kit was 96.5%. Therefore, 1% barium chloride can be utilized for the diagnosis of pregnancy in goats. Asian J. Med. Biol. Res. 2022, 8 (1), 42-46